REFORMING THE IDEAL ELECTION LAW THROUGH THE OMNIBUS LAW - Bakri, Rahmat; Sulbadana, Sulbadana; Supriyadi, Supriyadi; Purnamasari, Andi Intan (Cepalo, 2024)
The Omnibus Law concept consolidates multiple laws into a single legislative framework. In Indonesia, the regulation of elections is currently fragmented across separate laws for different types of elections and related sectoral laws. Consequently, various challenges often hamper its implementation. These challenges can be addressed by Omnibus Law which integrates all election-related laws into one comprehensive Election Law. This juridical-normative research examined this topic through legislative, conceptual, and case methods. The results of the analysis show that the Omnibus Law provides a solution to the overlapping regulations. In this context, Omnibus Law serves as a formal Gesetz within the legislative process and suggests that an ideal electoral system would merge the Election Law with relevant sectoral laws—such as the Population Administration Law, Political Party Law, Mass Organization Law, Administrative Court Law (PTUN), and Constitutional Court Law—into a unified legal framework.